Monocotyledonous plants graft at the embryonic root–shoot interface - Reeves, Gregory; Tripathi, Anoop; Singh, Pallavi; Jones, Maximillian R.W.; Nanda, Amrit K.; Musseau, Constance; Craze, Melanie; Bowden, Sarah; Walker, Joseph F.; Bentley, Alison R.; Melnyk, Charles W.; Hibberd, Julian M. (Springer, 2022)
Grafting is possible in both animals and plants. Although in animals the process requires surgery and is often associated with rejection of non-self, in plants grafting is widespread, and has been used since antiquity for crop improvement1. However, in the monocotyledons, which represent the second largest group of terrestrial plants and include many staple crops, the absence of vascular cambium is thought to preclude grafting2. Here we show that the embryonic hypocotyl allows intra- and inter-specific grafting in all three monocotyledon groups: the commelinids, lilioids and alismatids. We show functional graft unions through histology, application of exogenous fluorescent dyes, complementation assays for movement of endogenous hormones, and growth of plants to maturity. Expression profiling identifies genes that unify the molecular response associated with grafting in monocotyledons and dicotyledons, but also gene families that have not previously been associated with tissue union. Fusion of susceptible wheat scions to oat rootstocks confers resistance to the soil-borne pathogen Gaeumannomyces graminis. Collectively, these data overturn the consensus that monocotyledons cannot form graft unions, and identify the hypocotyl (mesocotyl in grasses) as a meristematic tissue that allows this process. We conclude that graft compatibility is a shared ability among seed-bearing plants.